Statistics with Stata - Hamilton, Lawrence C. (Thomson/BrooksCole, 2006)
Whether you're a student or practicing researcher, STATISTICS WITH STATA opens the door to the full use of the popular STATA program -a fast, flexible, and easy-to-use environment for data management and statistics analysis. Integrating STATA's impressive graphics, this comprehensive book presents hundreds of examples showing how you can apply Stata to accomplish a wide variety of tasks. Like STATA itself, STATISTICS WITH STATA will make it easier for you to move fluidly through the world of modern data analysis